O Largo de São Francisco e a Praça Tiradentes: sua importância e complementaridade na vida pública e cultural do Rio de Janeiro 1808-1920 - Cantanhede, Angela Tâmega Menezes (1998)
Presents a historical, architectural, urban and social analysis of the formation and development of two of the most tradicional public spaces of the city of Rio de Janeiro: São Francisco Plaza and Tiradentes Square. The aim of this work is to demonstrate the intrinsic relationship between social, cultural and urban life of these two public spaces and its importantance in the development of the city. The definition of the universe of this research results from its importance in the urban history of Rio de Janeiro and the role that it still represents as a structural element of the actual dinamics of the city as well as the complementary aspect that they have. The São Francisco Plaza is traditionally related to culture, accomodating buildings as The National Enginering School and one of the oldest churches of the city. On the other hand, Tiradentes Square has a profound link with several branches of show business with many traditional theatres sorrounding the place. This complementarity/cumplicity is what this work tries to demonstrate by a glancing at the urban dinamics of public spaces so realistic as these two and by considering the importance of the architecture and urbanism in the perspective each time more global of the ambiental sciences, where human life and physical environment, no matter whether natural or created, interact continuously and unceasingly. The social changes of the period have been observed through the contribution of the press, comments of writers and travellers as well as iconografic records of the period, by means of the way of life, the costums and the receptivity of the public at the time where the social changes had occured. This work analyses the two spaces in a complementary and paralel way,trying to detect the moments of simultaneity and integration. In this way, it was possible to define a period that begins with the arrival of the royal family at Rio de Janeiro when both spaces begin to have substancial importance on social and political life of the city, till the second decade of the XX century when these two places begin to demonstrate the firsts signs of physical and social decadence.